Kevin Corrigan, Evagrius and Gregory. Mind, Soul and Body in the 4th Century, Ashgate Studies in Philosophy and Theology in Late Antiquity, Farnham 2009, Wydawnictwo Ashgate, ss. 245. - Misiarczyk, Leszek (Vox Patrum, 2016)
nie dotyczy